Structural and optical properties of Ge60Te40: experimental and theoretical verification. (16th March 2016) - Yi, Xinyu; Wang, Zhanyu; Dong, Fei; Cheng, Shuai; Wang, Jun; Liu, Chaochao; Li, Jing; Wang, Songyou; Yang, Tieying; Su, Wan-Sheng; Chen, Liangyao
Abstract: The temperature-dependent structural and optical properties of Ge60 Te40 during transformation from amorphous to crystalline phases are studied by spectroscopic ellipsometry, grazing incidence x-ray diffraction (GIXRD), x-ray photoelectron spectroscopy (XPS), high resolution transmission electron microscopy (HRTEM) as well as ab initio molecular dynamics (MD) simulations. Our findings, derived from GIXRD results and dielectric functions, indicate that the crystallization process of Ge60 Te40 occurs at 260 °C and the crystalline phase adopts the rhombohedral GeTe phase along with the cubic Ge phase. Our calculations further indicate that the Ge atoms also prefer to clump together in amorphous Ge60 Te40 . Such a segregation of Ge leads to a high-temperature phase-change in Ge60 Te40 samples. According to the XPS results, the local atomic environment between amorphous and crystalline states gets a little bit of change. And the result of the atomic cluster alignment suggests that both the amorphous and crystalline phases have the rhombohedral local structure.